Legal Audit as an Effort to Improve Good Corporate Governance Based on Prudential Principles - Karuna, Indrayana Chandra; Sulistianingsih, Dewi; R. Suharto (Universitas Negeri Semarang, 2024)
Legal Audit or legal due diligence is a careful examination activity in terms of law which is conducted by legal consultants on a company in accordance with the purpose of the transaction. The purpose of this study is to analyze legal audits conducted in companies as an effort to improve good corporate governance with the principle of prudence. This study uses normative research methods, where the author examines and studies the norms governing legal audits in companies in accordance with applicable laws and regulations. Legal audit aims to assess the level of company security, especially in terms of risk aspects that can endanger assets owned by the company and to obtain information or material facts that can describe the condition of a company or object of transaction. Legal audit will be conducted very necessary, for example in the state that the company will mergers, acquisitions, consolidations, credit with third parties, to the sale of the company. Even for Initial Public Offering activities, each issuer is required to appoint an advocate in conducting an examination in terms of company law. In this audit/audit process, documents are required such as the deed of incorporation, documents related to company assets, board of directors meetings, and commissioners meetings, agreements made and signed by the company with other parties, documents related to licensing, taxes, labor affairs, company insurance, including documents related to the relationship between the company and court bodies and outside the court. This Legal Audit aims to verify the legality of a legal entity or business entity, determine the level of compliance of a legal entity with a rule of law, provide views on a plan/action to be taken by the company, and to obtain legal certainty on a legal issue.